PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN Koperasi Unit Desa (KUD) Pakis Malang - Liyanti Lidin; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect of competency and organizational commitment on employee job satisfaction of the Village Unit Cooperative (KUD) company in Malang. The type of research that aims to test a hypothesis to strengthen or reject an existing hypothesis. The sample and population in this study amounted to 35 people who were employees of the Village Unit Cooperative (KUD) Pakis Malang,The method used is descriptive data analysis, namely by using tests of validity, reliability, normality, multicollinearity test, heterocedasticity test, multiple linear analysis test f test, and hypothesis test t. The results of this study indicate that simultaneously each of the competency and organizational commitment variables equally has a positive  effect on job satisfaction, while partially the competency variable does not affect job satisfaction, and organizational commitment does not affect employee satisfaction at the performance of Koperasi Unit Desa (KUD) Pakis Malang” Keywords:       Influence Of Organizational Competence And Commitment On Employee Job Satisfaction